Correction to Phytotaxa 61: A synopsis of the species of Cyathea (Cyatheaceae-Polypodiopsida) with pinnate to pinnate-pinnatifid fronds - Lehnert, Marcus (Phytotaxa, 2013)
After the publication of the synopsis of simply pinnate species of Cyathea (Lehnert 2012), it was brought to my attention that I erroneously used Hemitelia munita Kuhn (1869: 162) as basionym for a variety in Cyathea grandifolia Willdenow (1810: 490) while there already was a validly published varietal name available that takes priority within that rank